Dental Implant Outcomes in Grafted Sockets: a Systematic Review and Meta-Analysis - Ausra Ramanauskaite; Tiago Borges; Bruno Leitão Almeida; Andre Correia (eJournal of Oral Maxillofacial Research)
Objectives: To assess the treatment outcomes of the dental implants placed in the grafted sockets.